POETRY DURING AND IMMEDIATELY AFTER THE WORLD WARS (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
The poetry produced during and immediately after the World Wars offers a vivid and poignant reflection of the horrors and human experiences shaped by conflict. During the First and Second World Wars, poets such as Wilfred Owen, Siegfried Sassoon, and Rupert Brooke captured the brutal realities of warfare, often in stark contrast to the idealized notions of patriotism and heroism. These poets, many of whom served on the frontlines, used their works to depict the suffering, disillusionment, and trauma caused by war. Their poems serve as a powerful protest against the glorification of war, offering instead an intimate and critical view of its devastating effects on individuals and society. In the aftermath of the wars, the poetry of this period continued to grapple with the legacy of destruction, capturing the profound psychological and emotional scars left on soldiers and civilians alike. Through their vivid imagery, innovative forms, and raw emotion, these poets shaped the cultural understanding of war and its aftermath, creating a body of work that remains relevant in exploring the moral and human costs of armed conflict.